(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The article proposes an administrative management strategy to strengthen educational inclusion in the Business Administration program at the University of Costa Rica, Guanacaste Campus. A mixed-methods approach and a descriptive-propositional design were employed, using questionnaires and participatory workshops involving students, faculty, and administrative staff. The results reveal structural, pedagogical, and administrative barriers that hinder students’ access, retention, and academic performance, particularly in regional contexts. The proposed strategy includes peer tutoring, curricular flexibility, and differentiated support protocols. It calls for a participatory and context-sensitive planning process aimed at reinforcing a more equitable, accessible, and inclusive university model that responds to the diverse needs of Costa Rican students.